Parallel computational fluid dynamics : parallel computing and its applications : proceedings of the Parallel CFD 2006 Conference, Busan city, Korea (May 15-18, 2006) /: parallel computing and its applications : proceedings of the Parallel CFD 2006 Conference, Busan city, Korea (May 15-18, 2006). (2007) - Unknown
No abstract available